2011
DOI: 10.1038/bmt.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Similar outcomes using myeloablative vs reduced-intensity allogeneic transplant preparative regimens for AML or MDS

Abstract: Although reduced intensity (RIC) and nonmyeloablative (NMA) conditioning regimens have been used for over a decade, their relative efficacy versus myeloablative (MA) approaches to allogeneic hematopoietic cell transplantation (HCT) in patients with acute myelogenous leukemia (AML) and myelodysplasia (MDS) is unknown. We compared disease status, donor, graft and recipient characteristics with outcomes of 3731 MA with 1448 RIC/NMA procedures performed at 217 centers between 1997 and 2004. Five year univariate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
199
4
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(226 citation statements)
references
References 25 publications
21
199
4
2
Order By: Relevance
“…It is then not surprising that even with age being significantly higher in the RIC group, this was not translated into worse outcomes. Other retrospective studies comparing RIC with MAC in AML have shown similar DFS and OS as in our analysis, but the increased relapse incidence usually associated with RIC was not found in the present report [16,30]. We also found that in-vivo T-cell depletion with ATG was not associated with an increased risk of relapse as it has been recently described [31].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is then not surprising that even with age being significantly higher in the RIC group, this was not translated into worse outcomes. Other retrospective studies comparing RIC with MAC in AML have shown similar DFS and OS as in our analysis, but the increased relapse incidence usually associated with RIC was not found in the present report [16,30]. We also found that in-vivo T-cell depletion with ATG was not associated with an increased risk of relapse as it has been recently described [31].…”
Section: Discussionsupporting
confidence: 78%
“…Cytogenetics affects similarly RIC and MAC with increased NRM and relapse incidence [30]. In our cohort restricted to very bad-risk leukemia, we observed a reasonable long-term survival, with a relapse incidence of 50%.…”
Section: Discussionsupporting
confidence: 52%
“…This study also identified poor risk cytogenetics, being in second versus in first CR, and conditioning with low-dose TBI-based RIC as being associated with worse LFS or OS, confirming previous reports. 18,31,32 Finally, our study demonstrated higher mortality in patients above 56 years of age at transplantation in comparison with younger patients, in contrast to what has been observed in a recent report from the CIBMTR analyzing data from 545 patients with AML given RIC allo-SCT, 18 perhaps because analyses were not adjusted for comorbidities at transplantation (more likely to be more frequent in older patients) in current study.…”
Section: Discussioncontrasting
confidence: 94%
“…(86)(87)(88)(89)(90)(91)(92)(93)(94)(95). During the prospective German-Austrian study (76), a growing number of patients received RIC-regimens.…”
Section: Predicting Counterbalancing Non Relapse Mortality (Nrm)mentioning
confidence: 99%